1973
DOI: 10.1524/ract.1973.19.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Hot Atom Reaction of 15O in Solids

Abstract: A number of years ago a few measurements were made to study the fate of atoms formed by the (n, 2n) reaction in solids of a simple composition. The materials were irradiated with fast neutrons in the IKO synchrocyclotron and dissolved in a suitable aqueous medium. Air was passed through the Solution to expel dissolved radioactive oxygen. The activities of the original material and the deaerated Solution were compared. (To exclude the possibility of radioactive oxygen gas escaping from the irradiated solid, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1975
1975
1981
1981

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a preliminary report [4] it was shown already that in some types of oxo-salts, in contrast to some Oxides [5] and sulphates [6] an appreciable fraction of the activity produced by the (n, 2n) reaction with fast neutrons can be recovered as molecular O'^O. It was observed [4] that salts of oxo-anions with high oxidation Potential tend to combine a high yield of 0' ^0, with high radiation chemical yields GCOj).…”
Section: Introductionmentioning
confidence: 99%
“…In a preliminary report [4] it was shown already that in some types of oxo-salts, in contrast to some Oxides [5] and sulphates [6] an appreciable fraction of the activity produced by the (n, 2n) reaction with fast neutrons can be recovered as molecular O'^O. It was observed [4] that salts of oxo-anions with high oxidation Potential tend to combine a high yield of 0' ^0, with high radiation chemical yields GCOj).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been reported in the literature on the production and uses of oxygen-15 as a radiotracer in chemistry [1,2] and in the life sciences [3,4,5]. The combination of pure positron emission {ß* = 1.74 MeV) and the relatively short physical life (r,/!…”
Section: Introductionmentioning
confidence: 99%